Perlindungan Konsumen Terhadap Investasi Emas Digital Ilegal di Indonesia Perspektif Undang-Undang Perlindungan Konsumen dan Hifz al-Mal - Mei Purnama Sari Siregar; Aida Nur Hasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of digital gold investment in Indonesia has made it easier for people to invest practically and flexibly. However, behind this convenience, various illegal digital gold investment practices have emerged that can be detrimental to consumers. This study aims to analyze the characteristics of illegal digital gold investment, legal protection for consumers, and its review from a Hifz al-Mal perspective. This study uses normative legal methods with legislative, conceptual, and comparative approaches. Data was obtained through literature review and qualitative analysis. The results indicate that illegal digital gold investments generally lack official permits, are non-transparent, and do not provide certainty regarding the underlying investment assets. These practices violate consumer rights as stipulated in Law Number 8 of 1999 concerning Consumer Protection. From a Hifz al-Mal perspective, these practices also contradict the principle of asset protection because they contain elements of gharar, tadlis, and maisir. Therefore, public supervision and education are necessary to ensure that digital gold investments operate safely and in accordance with Sharia law and principles.